Effect of varying the crop residue, cultivar and physical form on intake and nutrient utilization in Deccani sheep fed complete diets - Khan, A.A.; Sai, M.; Ravi, D.; Prasad, Kodukula V.S.V.; Anandan, S.; Ramana Reddy, Y.; Blümmel, Michael (Diva Enterprises Private Limited, 2016)
Four crop residue based complete diets (60R: 40C) with Andhra hybrid and Telangana sorghum stover, paddy straw and sweet sorghum bagasse with leaf residue (SSBLR) as sole roughage were formulated and processed into either mash or block form to study the effect of crop residue, cultivar and physical form on intake, nutrient utilization and N balance in growing Deccani ram lambs through metabolism trial. Fifty six Deccani ram lambs were randomly divided into eight groups of seven each and offered either block or mash form of the four crop residue based diets for a period of 25 d. DMI (g/d, g/kg BW or g/kg W0.75) of complete diet was not influenced by the type of crop residue or cultivar. Physical form of the diet had significant influence on DMI being higher (20–29%) in lambs fed mash than block diets irrespective of crop residue and cultivar. Digestibility of DM, OM, CP and cell wall constituents (NDF and ADF) was influenced by the type of crop residue and cultivar but physical form (mash vs. block) of the diet had no significant effect on nutrient digestibility except CP. Intake of OM, DOM, CP (g/d) and ME (MJ/d) was significantly higher in sheep fed mash form of diets than block form irrespective of cultivar and crop residue in the diet. Type of crop residue has no influence on nutrient intake except DOMI but cultivar in the complete diet had influence on nutrient intake either significantly (DOM, CP; P<0.05) or non-significantly (OM, ME) being higher in Andhra hybrid sorghum stover than Telangana stover based diet. N balance was influenced by the type of crop residue, cultivar and physical form of the diet. N balance was significantly (P<0.05) higher in mash than block, Andhra hybrid than Telangana cultivar and SSBLR and sorghum stover based diets than those fed paddy straw based diets. The results of the present study revealed that type and cultivar (quality) of crop residue and physical form of the diet had influence either significantly or non-significantly on intake, nutrient utilization and N balance in growing Deccani sheep fed complete diets.